Abrasion Resistance of Concrete Containing Polyolefin Fibers and Silica Fumes. Issue 5 (June 2014) - Cheng, An; Lin, Wei-Ting
This project is aimed to evaluate the abrasion resistance of cement-based composites which comprise polyolefin fibers and silica fume in the mixes. Material variables include water-binder ratio, dosage of silica fume and dosage of polyolefin fiber. Compressive strength, splitting tensile strength and abrasion tests were conducted and discussed. Test results indicate that the inclusion of polyolefin fiber or silica fume in cement-based composites not only increases the compressive strength and splitting tensile strength but also decreases the abrasion loss. The silica fume plays a positive rule on growth of compressive strength, splitting strength and abrasion resistance of cement-based composites due to the pozzolanic and filler effect. However, the distribution of fibers could not be controlled, resulting in a notable lack of uniformity in the specimens. The combination of silica fume and polyolefin fiber improves the strength properties and abrasion resistance than only use of polyolefin fiber. In addition, the modified Los Angeles abrasion test used in this study is suitable for the evaluation of abrasion resistance in cement-based composites. By regression analysis, the good correlations are found between compressive strength and splitting strength, abrasion ratio and compressive strength, and abrasion ratio and splitting strength.